A personal view of the early development of computational neuroscience in the USA - Moore, John W. (Frontiers in Computational Neuroscience, 2010)
In the half-century since the seminal Hodgkin–Huxley papers were published, computational neuroscience has become an established discipline, evolving from computer modeling of neurons to attempts to understand the computational functions of the brain. Here, I narrate my experience of the early steps and sense of excitement in this field, with its promise of rapid development, paralleling that of computers.